Interobserver variability in target volume delineation of hepatocellular carcinoma: an analysis of the working group “Stereotactic Radiotherapy” of the German Society for Radiation Oncology (DEGRO) - Gkika, Eleni; Häfner, Matthias (Strahlentherapie und Onkologie, 2017)
BackgroundDefinition of gross tumor volume (GTV) in hepatocellular carcinoma (HCC) requires dedicated imaging in multiple contrast medium phases. The aim of this study was to evaluate the interobserver agreement (IOA) in gross tumor delineation of HCC in a multicenter panel.MethodsThe analysis was performed within the “Stereotactic Radiotherapy” working group of the German Society for Radiation Oncology (DEGRO). The GTVs of three anonymized HCC cases were delineated by 16 physicians from nine centers using multiphasic CT scans. In the first case the tumor was well defined. The second patient had multifocal HCC (one conglomerate and one peripheral tumor) and was previously treated with transarterial chemoembolization (TACE). The peripheral lesion was adjacent to the previous TACE site. The last patient had an extensive HCC with a portal vein thrombosis (PVT) and an inhomogeneous liver parenchyma due to cirrhosis. The IOA was evaluated according to Landis and Koch.ResultsThe IOA for the first case was excellent (kappa: 0.85); for the second case moderate (kappa: 0.48) for the peripheral tumor and substantial (kappa: 0.73) for the conglomerate. In the case of the peripheral tumor the inconsistency is most likely explained by the necrotic tumor cavity after TACE caudal to the viable tumor. In the last case the IOA was fair, with a kappa of 0.34, with significant heterogeneity concerning the borders of the tumor and the PVT.ConclusionThe IOA was very good among the cases were the tumor was well defined. In complex cases, where the tumor did not show the typical characteristics, or in cases with Lipiodol (Guerbet, Paris, France) deposits, IOA agreement was compromised.